2021
DOI: 10.1007/s43546-021-00133-x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the efficiency of Tunisian bank branches using a stochastic frontier approach

Abstract: This article examines the efficiency scores of 94 Tunisian bank branches opening under the same public bank. It estimates the efficiency scores assigned to each bank branch using a model of the parametric method, namely the stochastic frontier approach (SFA). This method allows to isolate the term of random error, which reflects the inefficiency of each bank branch. Using data over the period 2007-2019, the paper shows that the branches of our sample present relatively similar levels of efficiency. It also ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Banks can improve efficiency in their operations by reducing operating expenses, developing branches' technical capabilities and increasing recovery rates (Islam et al, 2017). The early researches on bank efficiency focused mostly on European countries, the United States and Japan (Aissia and Ellouz, 2021). The non-parametric method (DEA) and the parametric approach (Stochastic Frontier Analysis [SFA]) were used in the existing literature to measure bank efficiency.…”
Section: Literature Review 21 Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Banks can improve efficiency in their operations by reducing operating expenses, developing branches' technical capabilities and increasing recovery rates (Islam et al, 2017). The early researches on bank efficiency focused mostly on European countries, the United States and Japan (Aissia and Ellouz, 2021). The non-parametric method (DEA) and the parametric approach (Stochastic Frontier Analysis [SFA]) were used in the existing literature to measure bank efficiency.…”
Section: Literature Review 21 Theoretical Backgroundmentioning
confidence: 99%
“…, 2017). The early researches on bank efficiency focused mostly on European countries, the United States and Japan (Aissia and Ellouz, 2021). The non-parametric method (DEA) and the parametric approach (Stochastic Frontier Analysis [SFA]) were used in the existing literature to measure bank efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their results indicate that the performance is higher for the banks with joint-equity holdings than the state-owned banks. Aissia and Ellouz ( 2021 ) also used SFA to estimate the efficiency of 94 branches of a Tunisian public bank for the period from 2007 to 2019 and found that efficiency levels among branches are rather similar. The annual TFP growth was 4.4% over the period 1993–2002.…”
Section: Studies On Bank Performancementioning
confidence: 99%